2018
DOI: 10.18203/2320-1770.ijrcog20184137
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, perceptions and practices of menstrual hygiene among degree college students in Guntur city of Andhra Pradesh, India

Abstract: Background: The unmet menstrual hygiene needs of young girls in India restrict their mobility and daily activities. Taboos and socio-cultural restrictions contribute to poor knowledge and practices leading to adverse health outcomes. This study is set to look at the knowledge, perceptions and practices concerning menstruation among college going girls.Methods: This study was conducted with 254-degree college students from a women’s degree college in Guntur city. After assuring adequate confidentiality, a self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 7 publications
1
23
0
3
Order By: Relevance
“…Similar findings are seen in other studies done by Balla et al where 13.4% girls have reported use of old clothes during menstruation 10. 88.7% girls used cloth in a study conducted by Dasgupta et al4 Another study done in Rajasthan by Khanna et al has found similar results regarding use of cloth during menstruation and ignorance towards sanitary pads.…”
supporting
confidence: 86%
“…Similar findings are seen in other studies done by Balla et al where 13.4% girls have reported use of old clothes during menstruation 10. 88.7% girls used cloth in a study conducted by Dasgupta et al4 Another study done in Rajasthan by Khanna et al has found similar results regarding use of cloth during menstruation and ignorance towards sanitary pads.…”
supporting
confidence: 86%
“…The researchers observed the prevalence of currently using menstrual pad varied in various studies. The findings were ranges from 56% to 100 among college or university students (6)(22)(51)(21). In the present study, around 18.9% used medication during menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…A study in India reported exclusive use of disposable absorbents was low among young women aged 15-24 (37%) and varied substantially by caste, education, wealth, and residence (20). However, study of uses of sanitary pads particularly among college students in India were 80 % (21),but uses were in Pakistan(22) and Ghana (6) were 77.5 % and 100% respectively. A study in Uttar Pradesh state of India among 10-19-year girls reported about half of the girls did not have information or knowledge about menstruation.…”
Section: Introductionmentioning
confidence: 99%
“…So, college students better use of menstruation hygiene practices than the general women population. A study in Telangana reported about 87 % of college students using sanitary pads (25), while a study done in Ghana said 100% were using a sanitary pad (26).…”
Section: Various State Governments Have a Provision In A School-basedmentioning
confidence: 99%